Fat’s loss is bone’s gain - Pei, Liming (J Clin Invest, 2004)
Osteoporosis, characterized by low bone mass and structural deterioration of bone tissue with an increased susceptibility to fractures, is a major public health threat to the elderly. Bone mass homeostasis in adults is maintained locally by the balance between osteoblastic bone formation and osteoclastic bone resorption. Haploinsufficiency of PPARγ, a key transcription factor implicated previously in adipogenesis, lipid metabolism, and glucose homeostasis, has now been shown to promote osteogenesis through enhanced osteoblast formation. These findings support a reciprocal relationship between the development of bone and fat, and may prompt further exploration of the PPAR pathway as a potential target for intervention in osteoporosis.